Understanding and managing service productivity: A literature review - Mirjam Dobmeier (jbm - Journal of Business Market Management, 2016)
Managers in service industries aim to achieve high efficiency and high quality at the same time to be profitable. This dual emphasis might lead to a trade-off as a focus on efficiency often results in decreasing service quality and vice versa. Even as this trade-off is generally acknowledged, research on service performance measurement often focuses only on either operational efficiency or service quality. A research stream that deals with the problem of achieving both efficiency and effectiveness is service productivity. This article gives a review on how service productivity is conceptually defined and empirically analyzed. The objective is to get a finer-grained understanding on service productivity, especially on how efficiency and effectiveness are interrelated ad which and how antecedents affect service productivity. In doing so, several insights on how to manage service productivity are given and several implications for further research are examined.
urn:nbn:de:0114-jbm-v9i1.1503
Keywords: 650; Service Productivity; Service Performance; Service Efficiency; Service Effectiveness